Peran Liga Arab terhadap Konflik Palestina dan Israel - Muhammad Diawan Masri (Diwan: Jurnal Bahasa dan Sastra Arab, 2022)
This study aims to see the world view of the two poets towards the Arab League on the conflict between Palestine and Israel, and how the role of the Arab League in the conflict between Palestine and Israel. The method used in this research is descriptive qualitative approach, with the type of library research. There are two types of data sources in this study, namely primary and secondary sources. The primary data sources were taken from the poem entitled "Ana Yusuf Ya Abi" by Mahmud Darwish quoted from Diwan"Al-A'mal Al-Ulaa 3", and "Al-Hub Wa Al-Bitrul" by Nizar Qabbani taken from Diwan Nizar Qabbani. The results of this study are the world view of the authors of these two poems as a form of expression of their disappointment, anxiety and restlessness towards the conflicts that occur in the Middle East in general, Palestine and Israel in particular. They see what is happening with Palestine as if they are not getting any meaningful help from the Arab League and other countries.